Preliminary Observations on Stem-flow, etc., in Alstonia scholaris and Shorea robusta Plantations at Arabari, West Bengal - Ray, Mukul P. (Indian Forester, 1970)
The paper presents the results of preliminary studies mainly on stem-flow and also on through-fall and interception in plantations of Alstonia scholaris and Shorea robusta, at Arabari in the East Midnapore Division of West Bengal. One plot each was laid out in the two species. Stem-flow, Through-fall and Interception were measured in each plot as a whole. Also stem-flow per tree (in litres) was measured for each girth class for the two species. The stem-flow in the lowest rainfall group, viz., 1-10 mm is greater in A. scholaris (20.4%) than in S. robusta (5.0%). The maximum stem-flow for the two species are 20.4% and 10.4%, respectively. For both the species, the gross stem-flow per tree increases with rainfall till saturation. For the same rainfall, stem-flow per tree increases as the girth class goes up, but it is greater in A. scholaris than in S. robusta. Through-fall for A. scholaris is 48.7% and that of S. robusta is 61.3% in the rainfall class 1-10mm. With increase in rainfall, through-fall increases in both the species but the difference decreases. For both the species, the Interception (%) figures are very close to each other. For the rainfall group 1-10 mm the values are 30.9% and 33.7% for the two species and decrease with increase in rainfall.